Holmium Laser Enucleation of the Prostate for Advanced Prostate Cancer-Related Bladder Outlet Obstruction: Assessing Effectiveness and Unraveling Factors Impacting Postoperative Urinary Incontinence - Hyeon Woo Kim; Jeong Zoo Lee; Tae Nam Kim; Dong Gil Shin (The World Journal of Men's Health, 2024)
Purpose: This study investigated the factors associated with transient urinary incontinence (TUI) after holmium laser enucleation of the prostate (HoLEP) as a palliative treatment in patients with severe bladder outlet obstruction (BOO) and advanced prostate cancer (PCA). Materials and Methods: Data of 28 patients with advanced PCA (≥cT3) who underwent palliative HoLEP between October 2018 and March 2021 were included in this retrospective study. After collection of the pre-, intra-, and postoperative (1, 3, and 12 months) data of patients from their medical records, variables of patients with and without TUI at 1 and 3–12 months postoperatively were statistically compared. Multivariate analysis was performed to investigate the factors associated with postoperative TUI. Results: Compared to baseline, the mean total international prostate symptom score, quality of life score, maximum flow rate (Qmax), and postvoid residual (PVR) were significantly improved 1 month postoperatively, and this was maintained until 12 months postoperatively (p<0.001). Of the 28 patients, 14 (50.00%) and 6 (21.43%) presented with TUI at 1 and 3–12 months postoperatively, respectively. Patients with TUI at 1 month follow-up showed a significantly lower preoperative Qmax (p=0.027), larger preoperative PVR (p=0.004), and higher likelihood of bladder neck tumor invasion (p=0.046). Conversely, patients with TUI at 3–12 months postoperatively were significantly older (p=0.033) and had a longer enucleation time (p=0.033). Multivariate analysis demonstrated that the factors affecting TUI were preoperative Qmax (odds ratio [OR]=0.61; 95% confidence interval [CI]=0.39–0.93; p=0.016) and bladder invasion of the tumor (OR=26.72; 95% CI=1.83–390.42; p=0.022) after 1 month; however, none of the variables correlated significantly with TUI at 3–12 months. Conclusions: Palliative HoLEP is an effective management option in patients with advanced PCA-related BOO. Lower preoperative Qmax and bladder neck tumor invasion are the factors affecting TUI at 1 month postoperatively.